TERAPI MUROTTAL SEBAGAI UPAYA MENURUNKAN KECEMASAN DAN TEKANAN DARAH PADA IBU HAMIL DENGAN PREEKLAMPSIA : LITERATURE REVIEW DILENGKAPI STUDI KASUS - Diki Retno Yuliani; Melyana Nurul Widyawati; Dyah Lustika Rahayu; Anita Widiastuti; Rusmini Rusmini (JURNAL KEBIDANAN, 2018)
The maternal mortality rate (MMR) in Indonesia is far from being the target of sustainable development goal's (SDG's), with one of the dominant causes being hypertension in pregnancy (HDK) such as preeclampsia. Pregnant women with preeclampsia are prone to experience anxiety, which if left untreated will have an effect on the welfare of the mother and baby. Anxiety can also cause blood pressure to raise. One relaxation technique to reduce anxiety and blood pressure is with murottal therapy. The purpose of this study was to determine the effect of murottal therapy in reducing anxiety and blood pressure in pregnant women with preeclampsia and to find out how to apply it to the case study. The research design used is literature review and case study. Samples for literature review were obtained from electronic databases, namely Google Scholar of 6 articles about the theme of Murottal and anxiety therapy (5 national and 1 international) and 8 articles on the theme of murottal therapy and blood pressure. Samples for case studies of 2 pregnant women with preeclampsia. The results obtained from the literature review include a decrease in anxiety scores before and after treatment with a mean reduction in anxiety scores 6,297, there is an effect of murottal therapy on blood pressure or there is a difference in blood pressure before and after getting treatment, the average decrease in mean systole 12,188 and average mean decrease in mean diastolic 6,233. Whereas the results obtained from the case study include risk factors for preeclampsia in the respondent is a history of hypertension, obesity and primipara; lack of knowledge or information and lack of optimal application of therapeutic communication is a factor that aggravates anxiety and; anxiety scores dropped after receiving murottal therapy and blood pressure also fell relative.